Nanocrystals and Nanostructures - Maria Simonescu, Claudia (IntechOpen, 2018)
Nanocrystals and nanostructures attract a special attention in the recent years due to their various properties and a wide range of applications such as in electrical, optical, optoelectronic, catalytic, medicine, chemo- and biosensing, and environmental protection fields. Although extensive research has been done in the field of nanocrystals, it is considered one growing research field. The main goal of this book is to present the current research activities in the field of nanocrystals and nanostructures covering issues regarding new synthesis methods, self-assembly strategies, characterization techniques, properties, and applications. Interesting reports regarding biomimetic modeling of the biomineralization processes and theoretical models to describe mechanisms of deformation twinning in nanocrystalline and ultrafine-grained materials have been presented. By structuring, approaching, and content, the work may be useful for specialist in the field of nano-/materials science, PhD students, students, and all those interested in this topic of high relevance.